2017
DOI: 10.1111/eci.12800
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D predictors in polycystic ovary syndrome: a meta-analysis

Abstract: Serum 25-hydroxyvitamin D may be predicted positively by serum calcium and negatively by luteinising hormone in women with PCOS, and negatively by waist-to-hip ratio and positively by fasting glucose in both PCOS and non-PCOS women, independently of the presence of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 31 publications
1
30
0
2
Order By: Relevance
“…Moreover, we found no evidence of any interaction between serum 25(OH)D levels and genetic variation in the vitamin D pathway on disease risk. Our finding that vitamin D deficiency associates independently with PCOS risk in women in Pakistan is consistent with reports from other settings including the Netherlands 10 , Iran 16 , Egypt 17 and the USA 18 , as well as with findings from a meta-analysis including these and other studies 19 , showing that mean 25(OH)D level was lower in women with PCOS than controls. The high prevalence of vitamin D deficiency seen among participants in the current study is in keeping with our previous study in Lahore showing a high prevalence of vitamin D deficiency among women of reproductive age 20 .…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, we found no evidence of any interaction between serum 25(OH)D levels and genetic variation in the vitamin D pathway on disease risk. Our finding that vitamin D deficiency associates independently with PCOS risk in women in Pakistan is consistent with reports from other settings including the Netherlands 10 , Iran 16 , Egypt 17 and the USA 18 , as well as with findings from a meta-analysis including these and other studies 19 , showing that mean 25(OH)D level was lower in women with PCOS than controls. The high prevalence of vitamin D deficiency seen among participants in the current study is in keeping with our previous study in Lahore showing a high prevalence of vitamin D deficiency among women of reproductive age 20 .…”
Section: Discussionsupporting
confidence: 91%
“…46 Additionally, the vitamin has been implicated in a number of pathologies affecting women, 7,8 including polycystic ovary syndrome (PCOS), 911 yet little is known about how it affects androgen homeostasis in premenopausal, eumenorrheic women.…”
mentioning
confidence: 99%
“…Similar vitamin D levels were detected in the present study in PCOS and control participants regardless of the presence of Apa-I SNP. Interestingly, while two meta-analyses [ 5 , 6 ] comprising 3182 and 2262 women respectively showed that serum 25(OH)D concentrations were lower in PCOS compared to controls, the reported standardized mean difference between the groups in both studies seems of little clinical relevance – only 0.74 ng/mL (95%IC: -1.26 to − 0.22) [ 5 ] and 0.64 ng/mL (95%IC: -1.12 to − 0.15) [ 6 ]. In turn, the fact that our PCOS patients with MetS had lower vitamin D levels and higher frequency of CC polymorphism compared to those without MetS suggests that the Apa-I gene variant might impact vitamin D levels in PCOS with MetS.…”
Section: Discussionmentioning
confidence: 99%
“…While its etiology remains unclear, PCOS is considered a polygenic and multifactorial disease, with metabolic, endocrine, and reproductive alterations [ 4 ]. In PCOS women, evidence suggests that vitamin D levels may be decreased and related to hormone and metabolic disturbances [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%